The Effect of Karkatibeejadi Churna by Internal Administration in Mutraghata with special reference to Benign Prostatic Hyperplasia - Shiji Mohan; M S Deepa; Remya V R (International Journal of Ayurveda and Pharma Research, 2023)
Benign Prostatic Hyperplasia is a non-malignant enlargement of the prostate gland caused by excessive growth of prostatic tissue. The main symptoms of BPH include hesitancy, frequency, urgency, weak stream urination, straining and nocturia. These together termed as LUTS. We cannot see a single disease in Ayurveda which shows all the features of benign prostatic hyperplasia. Mutragranthi is one among the 12 types of Mutraghatas which can be compared with benign prostatic hyperplasia due to its similarities in morphological, anatomical, and clinical features. Lower urinary symptoms in patients are very troublesome which affects their daily routine and sleep pattern and a negative impact on their quality of life. Embarrassment and the treatment cost prevent them to take timely treatment. In modern system of medicines, the treatment of BPH is done by conservative and surgical therapies. These methods have significant complications and are too expensive. Karkatibeejadi churna is mentioned in Bhaishajyaratnavali in Mutraghata prakarana. The ingredients of this Choorna are easily available and easy to prepare and consume. This case study was done in a participant of age 67 years with symptoms of benign prostatic hyperplasia which was confirmed by USG in search of an effective, cost effective conservative treatment. The Choorna was given for 60 days and assessments were done on 0th, 16th 31st, 46th and 61st days and the result showed significant reduction in symptoms, prostate volume and post void residual urine of benign prostatic hyperplasia.